2002
DOI: 10.1097/00006123-200211002-00023
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Percutaneous Posterior Lumbar Interbody Fusion

Abstract: OBJECTIVE The wide exposure required for a standard posterior lumbar interbody fusion (PLIF) can cause unnecessary trauma to the lumbar musculoligamentous complex. By combining existing microendoscopic, percutaneous instrumentation and interbody technologies, a novel, minimally invasive, percutaneous PLIF technique was developed to minimize such iatrogenic tissue injury (MIP-PLIF). METHODS The MIP-PLIF technique was validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
136
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 48 publications
1
136
0
4
Order By: Relevance
“…Preliminary results suggested that the MI posterior lumbar fusion procedures hold the promise of decreased iatrogenic muscle injury and approach-related morbidity, while allowing the surgeon to perform the operation as effectively as the conventional open surgery [8,11,13,20,22,25]. However, there was no long-term evaluation of changes in multifidus muscle and their potential effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary results suggested that the MI posterior lumbar fusion procedures hold the promise of decreased iatrogenic muscle injury and approach-related morbidity, while allowing the surgeon to perform the operation as effectively as the conventional open surgery [8,11,13,20,22,25]. However, there was no long-term evaluation of changes in multifidus muscle and their potential effects.…”
Section: Discussionmentioning
confidence: 99%
“…Later, with modifications of the tubular retractor system, this approach was utilized for posterior lumbar interbody fusion (PLIF), transforaminal LIF, and posterolateral LF. Preliminary results suggested that the minimally invasive approach is superior to the conventional open approach in terms of reduced intramuscular pressure and paraspinal muscle edema, [25] less blood loss, [8,11,20,22] lower serum creatinine kinase (CK) and inflammatory cytokine levels, [13] and less postoperative back pain [20,22]. Particularly, all of the midline supporting musculo-ligamentous structures are left intact with this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing technological progress led to the development of specific percutaneous surgical techniques to treat lumbar degenerative diseases [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive spine surgery techniques generally cause less "collateral damage" resulting in decreased blood loss, lower infection rates, quicker recovery, and shorter hospital stays. 5,8,9,11 Unfortunately, minimally invasive and open spine deformity surgeries have largely remained as two distinct subspecialties in spine surgery, with few surgeons who consider themselves proficient in both disciplines. Thus, until recently, the principles of minimally invasive surgery (MIS) were rarely applied to the treatment of ASD.…”
mentioning
confidence: 99%
“…The benefits of minimally invasive techniques (that is, MIS vs open transforaminal lumbar interbody fusion) have been demonstrated for degenerative disease over a short segment of the spine. 5,8,9 However, the indications, efficacy, and complications of minimally invasive techniques when applied to the treatment of spinal deformity have not been adequately compared with open procedures.…”
mentioning
confidence: 99%